Changing Features of the Automobile Industry in Asia:Comparison of Production, Trade and Market Structure in Selected Countries - Biswajit Nag; Saikat Banerjee; Rittwik Chatterjee (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
The global automotive industry, increasingly characterized by global mergers and relocation of production centers to emerging developing economies, is in the grips of a global price-war. The industry is subject to imperfect competition which has resulted in too much of everything — too much capacity, too many competitors and too much redundancy and overlap. The industry is concerned with consumer demands for styling, safety, and comfort; and with labor relations and manufacturing efficiency. In this context, the study examines the growth patterns, changes in ownership structures, trade patterns and role of governments of selected Asian countries (viz. China, India, Indonesia and Thailand) in the automobile sector.
Keywords: F1; 330; Automobile; Asia; Market Structure